Curcumin as a Natural Approach of Periodontal Adjunctive Treatment and Its Immunological Implications: A Narrative Review - Sorina Mihaela Solomon; Celina Silvia Stafie; Irina-Georgeta Sufaru; Silvia Teslaru; Cristina Mihaela Ghiciuc; Florin Dumitru Petrariu; Oana Tanculescu (Pharmaceutics, 2022)
Scaling and root planing represent the gold standard in the treatment of periodontal disease, but these therapeutic methods cannot eliminate the remaining periodontopathogenic bacteria in cement, tubules, and periodontal soft tissue. Thus, a number of additional therapeutic means have been adopted, including local and systemic antibiotic therapy, as well as the use of photodynamic therapy techniques. Recently, special attention has been paid to potential phytotherapeutic means in the treatment of periodontal disease. In this review, we aim to present the effects generated by the extract of Curcuma longa, the various forms of application of turmeric as an additional therapeutic means, as well as the aspects related to its biotolerance.